2012
DOI: 10.1001/archneurol.2011.3323
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal Dementia in Elderly Individuals

Abstract: To determine whether cases of frontotemporal lobar degeneration (FTLD) do exist in elderly individuals and have clinical and neuropathological features distinct from those with presenile onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 39 publications
6
38
1
1
Order By: Relevance
“…In all 16 expansion carriers, expansion size ranged from ∼5 kb (∼450 repeats) to in excess of 23 kb over 3600 repeats). No pathological variants of GRN , CHMP2B , TARDBP , FUS , MAPT haplotype and APOE alleles were found [18, 19]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all 16 expansion carriers, expansion size ranged from ∼5 kb (∼450 repeats) to in excess of 23 kb over 3600 repeats). No pathological variants of GRN , CHMP2B , TARDBP , FUS , MAPT haplotype and APOE alleles were found [18, 19]. …”
Section: Resultsmentioning
confidence: 99%
“…Although, their clinical features were ascertained retrospectively from clinical records, and as such should be treated with some caution, they do seem to show a fairly rapid cognitive decline in common. Two of these patients (patients 2 and 3) can clearly be regarded as late onset FTLD [19]. Patient 1 deteriorated rapidly and died after 10‐month duration of illness, without extensive clinical or neuropsychological follow‐up, although clinical observation led to the impression of FTLD.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that elderly patients with FTD often present with memory impairment. 5,23,24 In one autopsy study, 64% (n=7) of 11 elderly patients with FTD had anterograde memory loss. 23 Current treatment guidelines do not advise giving ChEIs or memantine treatments to FTD patients.…”
Section: Discussionmentioning
confidence: 99%
“…FTLD in elderly patients presents features of several phenotypes and morphologic subgroups similar to that seen in the presenile group, though patients with MAPT (tau-gene), but not GRN mutations or FUS pathology are rare or even absent [163]. However, these authors found significantly more frequent hippocampal sclerosis but milder frontal atrophy in the elder group [164], which was confirmed in two cases of FTLD tau aged 85 and 88 years, respectively [165]. Inclusions in FTLD-TDP and ALS but not in FTLD-FUS have properties of amyoid [166].…”
Section: Diagnostic Criteria For Other Dementiasmentioning
confidence: 89%